Rağıb El-İsfahani’nin insan ve ahlak anlayışı - Gafarov, Anar (My University, 2004)
Bu tezimizde Râgıb el-İsfahânî'nin insan ve ahlâk anlayışını ortaya koyduk. Ayrıca düşünürün ahlak konusundaki görüşlerini kendisinden önceki İslam filozoflarının görüşleriyle karşılaştırarak ele aldık. Araştırmamız giriş ve iki bölümden oluşmaktadır. Giriş kısmında Râgıb el-İsfahânî'nin hayatına ve eserlerine yer verdik. Birinci bölümde genel olarak ahlâk kavramını ve Râgıb el-İsfahânî'den önceki İslam filozoflarının ahlak felsefesini ele aldık. Tezimizde İsfahânî'den önceki ahlâk felsefesini Kindî, Fârâbî, İhvân-ı Safâ, İbn Sînâ ve İbn Miskeveyh'in görüşleriyle sınırladık. İkinci bölüm de kısımdan oluşmaktadır. Birinci kısmında Râgıb el-İsfahânî'nin insan anlayışını ikinci kısmında ise ahlâk anlayışını sunmuş bulunmaktayız. İnsan ve ahlâk görüşünü ortaya koymağa çalıştığımız Râgıb el-İsfahânî'nin ahlâk felsefesinin temel konusu insan ve mutluluktur. Düşünürün ahlak anlayışında akıl temel kriterdir. Onun ahlak felsefesi ahlâkla ilgili yüz üç kavramı içermektedir. In this thesis I have dealt with al-Isfahânî's conception of human and his view of ethic depending upon his writings. Furthermore, I have compared his view with other Islamic philosophers who worked on these issues before him. . This thesis consists of an introduction and two chapters. In introduction, I have brought out a biography of Isfahani and I have enumerated a list of his works together with a brief explanation. In first chapter, I have dealt with the concept of ethics and philosophy of ethics in the writings of Islamic philosophers in general. I have concentrated on moral philosophy which was demonstrated in the writings of Kindi, Farabi, Ihvan as-Safa, Ibn Sina and Ibn Miskeveyh who were taken the same issue before Isfahani.. In the second chapter, I have argued the conception of human as well as his understandings of ethics relying on Isfahani's writings. The core of his moral philosophy depends on the important concepts that are of human and happiness. In his moral philosophy, reason which is considered as a basic criterion, plays a dispensable role. In relation with ethics, al-Isfahanî deals with more than three concepts.
Keywords: Felsefe, İslam